Clyde P. Fisher Science Hall Dedication (1978)
[00:00:00] Audience chatter [00:00:15] Beginning of speech [00:01:13] Speaker begins introductions of off-campus personnel directly involved in the construction of the building [00:04:40] Vice President Hazel Jones begins to speak about the long process of constructing the building and how it will benefit the science departments [00:07:30] Jones speaks about how important science is to all curriculums, not only those directly involved [00:08:00] Jones introduces Dean Langworthy [00:09:00] Langworthy discusses memories about working with Dean Fisher [00:11:30] Langworthy talks about the amenities included in the building and how this will solve many of the problems currently faced by the department [00:14:43] Emcee introduces President Robert E. Kennedy to talk about career and greatness of Clyde Fisher [00:21:15] Emcee introduces Milo Witson to present the Fisher portrait to the university [00:23:00] Witson describes the production process of the portrait [00:26:20] Robert E. Kennedy and Helen Fisher accept the portrait as a gift [00:26:35] Helen Fisher thanks all the university faculty and audience for the portrait, building, and respect for Clyde Fisher [00:31:00] Emcee introduces John Hampton [00:31:20] Cut in tape between sides one and two [00:31:38] John Hampton announces lecture series and tours of the building taking place after the benediction [00:33:00] C. William Fisher, Clyde's brother, gives the benediction [00:37:05] Emcee closes ceremony and directs people to tours